Zirconium oxide powder, zirconia-based composite oxide dielectric, and zirconia-based composite oxide dielectric powder
Patent Information
- Application Number
- JP2023126954
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0018】 本発明によれば、ジルコニア系複合酸化物誘電体を比較的低温で合成することができる酸化ジルコニウム粉末を提供することができる。
Smart Images

Figure 2025022412000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a zirconium oxide powder, a zirconia-based composite oxide dielectric material, and a zirconia-based composite oxide dielectric material powder. [Background technology]
[0002] A multi-layer ceramic capacitor (MLCC) has a structure in which a large number of dielectric layers and internal electrode layers made of ceramic are laminated. In recent years, as electronic devices become smaller and lighter, MLCCs have become smaller and thinner (for example, Patent Document 1), and this has led to an increased need for finer particles of the dielectric material that is the raw material for the dielectric layers.
[0003] An example of a dielectric material used in the manufacture of MLCCs is a perovskite-type dielectric material having a perovskite crystal structure (for example, Patent Document 2). This perovskite-type dielectric material is represented by the chemical formula ABO3, where metal A is a divalent metal ion such as Ca, Sr, Ba, etc., and metal B is a tetravalent metal ion such as Ti, Zr, etc. An MLCC using such a dielectric material is also called a temperature-compensated MLCC, and is used when precision in capacitance is required, such as in tuning circuits, oscillation circuits, and high-frequency filter circuits, because the change in capacitance caused by changes in temperature or applied voltage is small.
[0004] An example of the perovskite type dielectric as described above is a zirconia-based composite oxide dielectric, which is represented by the above-mentioned chemical formula: AZrO3. The zirconia-based composite oxide dielectric can be obtained, for example, by mixing zirconium oxide powder with a powder of a compound of metal A (e.g., calcium carbonate) in a wet ball mill or the like, drying the slurry, and firing it. Here, for example, methods disclosed in Patent Document 3 and Patent Document 4 are methods for producing zirconium oxide, which is the raw material of the zirconia-based composite oxide dielectric. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-28254 A [Patent Document 2] JP 2015-195352 A [Patent Document 3] JP 2019-202901 A [Patent Document 4] JP 2007-15898 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the firing process for the manufacture of zirconia-based composite oxide dielectrics, zirconium and metal A are mutually diffused and uniformly solid-dissolved, which promotes the synthesis of the dielectric, but the firing process must be carried out at a very high temperature. When firing at such a high temperature, the dielectric particles produced grow, which is a problem in that the dielectric particles cannot be finely divided. In addition, the firing temperature is so high that it is difficult to suppress the firing cost.
[0007] Therefore, the present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a zirconium oxide powder that can synthesize a zirconia-based composite oxide dielectric at a relatively low temperature. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by using a zirconium oxide powder having a maximum carbon dioxide desorption temperature of 520°C or higher, which has led to the completion of the present invention.
[0009] That is, the above objects can be achieved by the present invention having the following configuration, and the present invention includes the following aspects and configurations.
[0010] One aspect of the present invention is 1. Zirconium oxide powder with a maximum carbon dioxide desorption temperature of 520°C or higher.
[0011] 2. In the zirconium oxide powder according to the above item 1, the amount of carbon dioxide released from 25° C. to 1000° C. is 0.4 mass % or more.
[0012] 3. In the zirconium oxide powder described in 1 or 2 above, it is preferable that the maximum peak of the carbon dioxide desorption rate in the temperature programmed desorption spectrum of carbon dioxide is 100° C. or lower.
[0013] 4. In the zirconium oxide powder according to any one of 1. to 3. above, the maximum peak of the carbon dioxide desorption rate is preferably 5.0 mass ppm / sec or more.
[0014] 5. The zirconium oxide powder according to any one of 1. to 4. above, wherein the BET specific surface area is 80 m 2 It is preferable that the molecular weight is 1 / g or more.
[0015] One aspect of the present invention is 6. A zirconia-based composite oxide dielectric material made from the zirconium oxide powder according to any one of 1. to 5. above.
[0016] 7. The zirconia-based composite oxide dielectric material described in 6 above preferably contains calcium.
[0017] One aspect of the present invention is 8. A zirconia-based composite oxide dielectric powder comprising the zirconia-based composite oxide dielectric according to 6. or 7. above. Effect of the Invention
[0018] According to the present invention, it is possible to provide a zirconium oxide powder that can synthesize a zirconia-based composite oxide dielectric at a relatively low temperature. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a temperature programmed desorption spectrum of carbon dioxide in a zirconium oxide powder according to one embodiment of the present invention. [Diagram 2] FIG. 2 shows the results of evaluation of the zirconia-based composite oxide dielectric material according to one embodiment of the present invention by X-ray diffraction. [Diagram 3] FIG. 3 shows the results of evaluating the zirconia-based composite oxide dielectrics according to Comparative Example 1 and Comparative Example 2 by X-ray diffraction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention relates to a zirconium oxide powder having a maximum carbon dioxide desorption temperature of 520° C. or higher. The zirconium oxide powder according to one embodiment of the present invention having such a configuration allows for the synthesis of a zirconia-based composite oxide dielectric at a relatively low temperature.
[0021] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to only the following embodiment. In addition, in this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20°C to 25°C) and relative humidity of 40% RH to 50% RH.
[0022] [Zirconium oxide powder] The zirconium oxide powder according to one embodiment of the present invention has a maximum carbon dioxide desorption temperature of 520°C or higher. Since the maximum carbon dioxide desorption temperature is 520°C or higher, a zirconia-based composite oxide dielectric made from the zirconium oxide powder as a raw material can be fired and synthesized at a relatively low temperature. Since the zirconia-based composite oxide dielectric is synthesized at a relatively low temperature, the grain growth of the generated dielectric particles can be suppressed, enabling fine particle size reduction. Furthermore, since the firing temperature is relatively low, the cost required for synthesizing the dielectric can be suppressed.
[0023] Here, zirconium oxide powder means a powder mainly composed of zirconium oxide (ZrO2). As long as the zirconium oxide powder is mainly composed of zirconium oxide, the zirconium oxide powder may contain other components. The ratio of zirconium oxide contained in the zirconium oxide powder is preferably 85 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, particularly preferably 98 mass% or more, and most preferably 100 mass% based on the total mass of the zirconium oxide powder. Examples of other components include hafnium oxide.
[0024] The reason why the zirconia-based composite oxide dielectric material according to one embodiment of the present invention is synthesized at a relatively low temperature using the zirconium oxide powder as a raw material is not clear in detail, but it is believed to be as follows.
[0025] As described above, the zirconia-based composite oxide dielectric can be obtained, for example, by mixing zirconium oxide powder and powder of a compound of metal A (e.g., calcium carbonate, etc.) in a wet ball mill or the like, drying the slurry, and then firing. In conventional zirconium oxide, OH groups on the particle surface undergo dehydration condensation during firing, causing aggregation of zirconium oxide particles. This prevents mutual diffusion between zirconium and metal A (e.g., calcium), and also prevents uniform solid solution. In order to obtain a zirconia-based composite oxide dielectric in a state in which such aggregation of zirconium oxide particles occurs, it is necessary to perform firing at a very high temperature to promote mutual diffusion and solid solution between zirconium and metal A.
[0026] On the other hand, the zirconium oxide powder according to one embodiment of the present invention has a higher maximum temperature of carbon dioxide desorption than conventional ones, and therefore a large amount of carbon dioxide is adsorbed on the particle surface. Therefore, in the zirconium oxide powder according to the present invention, the OH groups on the particle surface are covered with carbon dioxide, and dehydration condensation between the OH groups is unlikely to occur during firing of the zirconia-based composite oxide dielectric, and it is believed that the aggregation of zirconium oxide particles can be suppressed. As a result, even if the firing temperature is relatively low, the mutual diffusion between zirconium and metal A proceeds smoothly, and the two are uniformly dissolved in a solid solution, so that the zirconia-based composite oxide dielectric can be synthesized at a relatively low temperature.
[0027] In addition, the zirconium oxide powder according to one embodiment of the present invention has a larger amount of carbon dioxide adsorbed on the particle surface than conventional ones, so that when mixed with a powder of a compound of metal A (e.g., calcium carbonate, etc.) in a wet ball mill or the like, or when drying the slurry, the zirconium oxide particles can be prevented from agglomerating together. As a result, the zirconium oxide powder of the present invention can be uniformly mixed with a powder of a compound of metal A, and it is believed that interdiffusion between zirconium and metal A during firing proceeds effectively, allowing a uniform solid solution to be formed. This is also believed to be one of the reasons why a zirconia-based composite oxide dielectric can be synthesized at a relatively low temperature.
[0028] It should be noted that the above mechanism is merely speculation, and the present invention is not limited to the above mechanism.
[0029] [Maximum temperature for carbon dioxide desorption] The maximum temperature at which carbon dioxide desorption occurs in the zirconium oxide powder according to one embodiment of the present invention is calculated based on the results of measurement by the temperature programmed desorption-mass spectrometry (TPD-MS) method described below.
[0030] (TPD-MS method) The TPD-MS method is a method in which a mass spectrometer is directly connected to a special heating device with a temperature controller, and the change in concentration of gas generated from a sample during heating is tracked as a function of temperature and time. In this specification, the TPD-MS method is carried out according to the following procedure. First, 50 mg of zirconium oxide powder is placed in a glass tube passed through an electric furnace of a heating device with a temperature controller, and high-purity helium (He) gas is flowed at 50 cc / min for 15 minutes. Next, the temperature is raised to about 1000°C at a heating rate of 10°C / min in a simulated air (20% O2 / He) atmosphere, and the amount of carbon dioxide gas generated during the heating (m / z=44) is continuously measured using a mass spectrometer (Shimadzu Corporation, GCMS-QP2020). The measurement results can be represented, for example, by a graph showing temperature (°C) on the horizontal axis and the carbon dioxide generation rate (mass ppm / sec) on the vertical axis (see FIG. 1). In this specification, the graph is called a temperature-programmed desorption spectrum.
[0031] The maximum carbon dioxide desorption temperature refers to the temperature at which the carbon dioxide generation rate (ppm by mass / sec) reaches its maximum peak and then becomes less than 0.01 ppm by mass / sec for the first time, as measured by the TPD-MS method. Here, the carbon dioxide generation rate is a value measured by the TPD-MS method, and refers to the amount of carbon dioxide (ppm by mass) generated from the zirconium oxide powder per unit time (1 second).
[0032] The maximum carbon dioxide desorption temperature of the zirconium oxide powder according to one embodiment is 520° C. or higher, preferably 525° C. or higher, more preferably 530° C. or higher, even more preferably 535° C. or higher, even more preferably 540° C. or higher, and particularly preferably 543° C. When the maximum desorption temperature is in the above range, aggregation of the zirconium oxide powder can be more effectively prevented. The upper limit temperature can be practically 700° C. or lower.
[0033] [Amount of carbon dioxide released] In this specification, the carbon dioxide desorption rate (mass %) is a value obtained by dividing the total mass of carbon dioxide measured in a predetermined temperature rise interval in measurement by the TPD-MS method (in other words, the total mass of carbon dioxide desorbed from the zirconium oxide powder within a predetermined temperature rise interval) by the mass of the zirconium oxide powder at 25°C before measurement by the same method. The total mass of carbon dioxide measured in a predetermined temperature rise interval can be calculated, for example, by integrating the carbon dioxide generation rate (mass ppm / sec) measured in that interval.
[0034] In one embodiment of the zirconium oxide powder, the amount of carbon dioxide desorption from 25° C. to 1000° C. is preferably 0.4% by mass or more, more preferably 0.5% by mass or more, even more preferably 0.6% by mass or more, and particularly preferably 0.7% by mass or more. The upper limit of the amount of carbon dioxide desorption from the zirconium oxide powder from 25° C. to 1000° C. is not particularly limited, but is preferably 5% by mass or less, more preferably 2.5% by mass or less. When the amount of carbon dioxide desorption from 25° C. to 1000° C. is within the above range, the amount of carbon dioxide present on the zirconium oxide surface becomes more sufficient, and the aggregation of zirconium oxide particles during firing can be more sufficiently suppressed, so that the effects of the present invention can be more effectively exhibited.
[0035] [Maximum peak of carbon dioxide desorption rate] In the zirconium oxide powder according to one embodiment, the maximum peak of the carbon dioxide desorption rate in the above-mentioned carbon dioxide temperature-programmed desorption spectrum is preferably 100° C. or less. When the maximum peak of the desorption rate is 100° C. or less, the effect of being able to synthesize a zirconia-based composite oxide dielectric at a low temperature and / or the effect of being able to synthesize a zirconia-based composite oxide dielectric in a single phase (i.e., unreacted raw materials are less likely to remain after firing) can be more efficiently obtained. A large amount of carbon dioxide is adsorbed by a relatively weak bond in a zirconium oxide powder having a maximum peak of the desorption rate of 100° C. or less, and such a zirconium oxide powder has a high affinity with a compound of metal A and tends to be mixed homogeneously, so that the above-mentioned effect is presumed to be obtained. The lower limit of the temperature at the maximum peak of the carbon dioxide desorption rate is not particularly limited, but is preferably 60° C. or more, and more preferably 70° C. or more.
[0036] In addition, the carbon dioxide desorption rate at the maximum peak in the carbon dioxide temperature programmed desorption spectrum is preferably 5.0 mass ppm / sec or more, more preferably 6.0 mass ppm / sec or more, even more preferably 7.0 mass ppm / sec or more, and particularly preferably 8.0 mass ppm / sec or more. In addition, the upper limit of the carbon dioxide desorption rate at the maximum peak is not particularly limited, but is preferably 20 mass ppm / sec or less. When the carbon dioxide desorption rate at the maximum peak is in the above range, the amount of carbon dioxide present on the zirconium oxide surface becomes more sufficient, and the aggregation of zirconium oxide particles during firing in synthesizing the zirconia-based composite oxide dielectric can be more sufficiently suppressed, so that the effects of the present invention can be more effectively exhibited.
[0037] [BET specific surface area] The zirconium oxide powder according to one embodiment has a BET specific surface area of 80 m 2 / g or more, and 2 / g or more is more preferable, and 100m 2 More preferably, it is 120m / g or more. 2It is particularly preferable that the BET specific surface area is at least 300 m / g. By having the BET specific surface area be at the above lower limit, the amount of carbon dioxide present on the zirconium oxide surface becomes more sufficient, and furthermore, the zirconium oxide powder has the fineness required for a raw material for a dielectric material. On the other hand, the upper limit of the BET specific surface area is not particularly limited, but from the viewpoint of the crystallinity of the zirconium oxide, it is preferable that the upper limit of the BET specific surface area is 300 m / g or more. 2 / g or less, and 2 / g or less is more preferable, and 200m 2 It is more preferable that the molecular weight is not more than 1 / g.
[0038] The BET specific surface area in the present invention is a value measured by a single-point BET method using nitrogen gas as an adsorbate in accordance with JIS R 1626: 1996. More specifically, it is a value measured by the method described in the Examples.
[0039] [Average primary particle size] The average primary particle size of the zirconium oxide powder according to one embodiment is preferably 3.0 nm to 15.0 nm, more preferably 4.2 nm to 12.0 nm, and further preferably 5.2 nm to 8.8 nm. When the average primary particle size is within the above range, the zirconium oxide powder can be a suitable raw material for dielectric materials.
[0040] The average primary particle size is a particle size calculated from the BET specific surface area using the following relational expression.
[0041] Relationship: D = 6 / (ρ × S) D: Particle size (diameter) [μm] S:BET specific surface area [m 2 / g] ρ: true density [g / cm 3 ](Zirconium oxide: 5.68[g / cm 3 ]).
[0042] [Method of manufacturing zirconium oxide powder] The zirconium oxide powder according to one embodiment of the present invention is not particularly limited, but can be produced, for example, by the following method. That is, one embodiment of the present invention is a method for producing a zirconium oxide powder, which includes (A) a first step of obtaining a zirconium oxide precursor by a wet reaction, and (B) a second step of obtaining a zirconium oxide powder by calcining the zirconium oxide precursor.
[0043] <1st process> The first step in the method for producing zirconium oxide powder is to obtain a zirconium oxide precursor by a wet reaction.
[0044] More specifically, the first step includes (i) a dissolving step of dissolving a zirconium salt in a solvent to obtain a stock solution, (ii) a slurry obtaining step of adding a soluble carbonate to the stock solution to obtain a slurry, and (iii) a filtration and washing step of filtering and washing the slurry.
[0045] (melting process) The first step includes (i) a dissolving step of dissolving a zirconium salt in a solvent to obtain a stock solution. Hereinafter, the solution obtained by dissolving the zirconium salt in the solvent in this step is referred to as the stock solution.
[0046] Specific examples of zirconium salts used in the dissolution process include zirconium oxychloride octahydrate (ZrCl2O·8H2O), zirconium nitrate dihydrate (ZrO(NO3)2·2H2O), zirconium sulfate tetrahydrate (ZrSO4·4H2O), and zirconium oxyacetate (ZrO(CH3COO)2). These may be used alone or in combination of two or more. Of these, zirconium oxychloride octahydrate is preferably used from the viewpoint of safety and ease of treatment of wastewater and exhaust gas components generated in the production process.
[0047] In addition, from the viewpoints of the production volume per batch during industrial production and the density of precipitate particles when the precipitate particles are generated, the zirconium salt is dissolved in the solvent so that the concentration of zirconium oxide in the original solution (zirconium solution) is preferably 20 g / l to 150 g / l, more preferably 30 g / l to 100 g / l, and even more preferably 40 g / l to 70 g / l.
[0048] The solvent is not particularly limited, but is preferably water, and more preferably ion-exchanged water, from the viewpoint that the solvent is unlikely to evaporate when the stock solution is heated, i.e., the solvent has a high boiling point.
[0049] (Slurry obtaining process) The first step includes (ii) a slurry obtaining step of adding a soluble carbonate to the raw solution to obtain a slurry. By including this step, carbon dioxide can be sufficiently adsorbed on the particle surfaces of the zirconium oxide powder obtained by the manufacturing method. As a result, when the zirconium oxide powder of one embodiment of the present invention is used as a raw material, a zirconia-based composite oxide dielectric can be synthesized at a relatively low temperature.
[0050] The soluble carbonate used in the slurry obtaining step is not particularly limited, but is preferably at least one of ammonium carbonate and ammonium bicarbonate. The soluble carbonate may be added to the stock solution as a solid, or may be added to the stock solution as a solution dissolved in a solvent such as hydrochloric acid or nitric acid.
[0051] The amount of soluble carbonate added to the stock solution is preferably 0.1% by mass to 50% by mass, more preferably 0.5% by mass to 25% by mass, and even more preferably 0.8% by mass to 10% by mass, based on the total amount of the stock solution and the soluble carbonate or the total amount of the stock solution and the soluble carbonate solution. By adding the amount of soluble carbonate within the above range, carbon dioxide can be more sufficiently adsorbed onto the particle surfaces of the zirconium oxide powder obtained by the production method.
[0052] In the slurry obtaining step, the temperature of the raw solution when the soluble carbonate is added is preferably 50°C to 120°C, and more preferably 60°C to 100°C.
[0053] The pH of the slurry obtained in the slurry obtaining step is preferably 7.0 to 12.0, more preferably 8.0 to 11.0, and even more preferably 8.5 to 10.0. By having the pH in this range, more carbon dioxide can be dissolved in the slurry. The pH of the slurry can be adjusted by any method, but is preferably adjusted using a neutralizing agent. Examples of the neutralizing agent include organic amines such as ammonia, ethanolamine, triethanolamine, dimethylaminoethanol, and quaternary amines, but are not limited thereto.
[0054] (Filtering and washing process) The first step includes (iii) a filtering and washing step of filtering and washing the slurry. By including this step, a precipitate of a zirconium oxide precursor containing almost no impurities such as chloride ions can be obtained. The method of filtering and washing the slurry is not particularly limited, but for example, the following method can be adopted.
[0055] First, the slurry obtained in the slurry obtaining step is filtered through a filter cloth or filter paper using a device or instrument such as a filter press or a Buchner funnel to separate the solid components (filtration process). Next, the obtained solid components are repulped and washed with ammonia water (e.g., 10% ammonia water) or ion-exchanged water (washing process). This filtration process and washing process are performed multiple times in this order, and finally, a filtration process is performed to obtain a precipitate of a zirconium oxide precursor. <2nd process> The second step is a step of obtaining zirconium oxide powder by calcining the zirconium oxide precursor.
[0056] Here, the calcination treatment is preferably carried out in an atmosphere containing carbon dioxide. By calcining in the presence of carbon dioxide, a sufficient amount of carbon dioxide can be adsorbed on the particle surfaces of the zirconium oxide.
[0057] The atmosphere containing carbon dioxide may be realized by flowing carbon dioxide. For example, the firing process can be performed while flowing carbon dioxide into the heating device. The flow rate of carbon dioxide into the heating device is preferably 50cc / min to 500cc / min, and more preferably 100cc / min to 350cc / min.
[0058] The atmosphere containing carbon dioxide may be an air atmosphere, or may be realized by carbon dioxide generated from a burner or the like of a heating device. As the heating device, existing devices such as a batch-type electric furnace, a continuous furnace, a tubular furnace, etc. may be appropriately used. Here, the carbon dioxide generated from the burner or the like of the heating device is less than 50 cc / min.
[0059] The firing process includes a temperature increasing step of heating from room temperature to a target temperature (hereinafter referred to as the firing temperature) and a holding step of maintaining the firing temperature. Here, the firing temperature is preferably 200° C. to 600° C., and more preferably 250° C. to 500° C. By keeping the firing temperature within the above range, the crystallinity of the produced zirconium oxide is excellent, and grain growth of the zirconium oxide particles can be prevented.
[0060] The temperature-raising step in the firing is preferably performed for 2 to 10 hours, and the holding step is preferably performed for 2.5 to 5 hours. By performing the temperature-raising step and the holding step within the above time ranges, grain growth and aggregation of zirconium oxide particles can be prevented, and the zirconium oxide powder becomes suitable for producing a zirconia-based composite oxide dielectric.
[0061] (drying process) In one embodiment of the method for producing a zirconium oxide powder, the moist zirconium oxide precursor produced in the first step can be directly subjected to the second step, but it is preferable to have a drying step for drying the zirconium oxide precursor between the first and second steps.
[0062] The drying method in the drying step is not particularly limited, but is preferably performed by heat-treating the zirconium oxide precursor in an atmosphere containing carbon dioxide. By heat-treating in an atmosphere containing carbon dioxide, the amount of carbon dioxide adsorbed on the surface of the zirconium oxide precursor can be made more sufficient. Furthermore, drying by heat treatment shortens the drying time, and the productivity of the zirconium oxide powder can be improved.
[0063] The drying step in an atmosphere containing carbon dioxide can be realized, for example, by heat-treating the zirconium oxide precursor in an air atmosphere, but is more preferably realized by heat-treating the zirconium oxide precursor while flowing carbon dioxide into a dryer. The flow rate of carbon dioxide into the dryer is preferably 50cc / min to 500cc / min, and more preferably 75cc / min to 300cc / min. By keeping the flow rate of carbon dioxide within the above range, the amount of carbon dioxide adsorbed on the surface of the zirconium oxide precursor can be made more sufficient.
[0064] The heat treatment in the drying step is not particularly limited, but is preferably carried out at a temperature lower than 200° C., for example, 80° C. to 150° C., and more preferably 90° C. to 120° C. In addition, the heat treatment is not particularly limited, but is preferably carried out for 1 hour to 24 hours, and more preferably 3 hours to 12 hours.
[0065] (Crushing process) In one embodiment, the method for producing a zirconium oxide powder may include a milling step of milling zirconium oxide to adjust the particle size after the second step. The milling method is not particularly limited, and a stamp mill, roller mill, jet mill, media mill, vibration mill, ball mill, or the like that are typically used industrially can be used.
[0066] (How to store zirconium oxide powder) The zirconium oxide powder produced by the production method in one embodiment is preferably stored in an atmosphere containing carbon dioxide. By storing in such an atmosphere, the state in which carbon dioxide is sufficiently adsorbed on the surface of the zirconium oxide can be maintained. In one embodiment, the zirconium oxide powder is stored in an atmosphere adjusted to a carbon dioxide concentration higher than that of the air.
[0067] [Application] As described above, the zirconium oxide powder according to one embodiment of the present invention can be suitably used for synthesizing a zirconia-based composite oxide dielectric. That is, one embodiment of the present invention is a zirconia-based composite oxide dielectric using the zirconium oxide powder as a raw material.
[0068] In this specification, the zirconia-based composite oxide dielectric is a compound represented by the chemical formula AZrO3. Here, A is a Group II element, and is preferably calcium, strontium, or barium. That is, for example, calcium zirconate, strontium zirconate, and barium zirconate are suitable as the zirconia-based composite oxide dielectric. These may be used alone or in combination of two or more.
[0069] Among them, from the viewpoint of the temperature change of the relative dielectric constant of the dielectric and the magnitude of the dielectric constant, the zirconia-based composite oxide dielectric according to one embodiment more preferably contains calcium, i.e., the zirconia-based composite oxide dielectric is more preferably calcium zirconate.
[0070] The zirconia-based composite oxide dielectric according to one embodiment of the present invention can be synthesized by a known method using the zirconium oxide powder according to one embodiment of the present invention. For example, the zirconia-based composite oxide dielectric according to one embodiment of the present invention can be synthesized by firing a mixture of the zirconium oxide powder according to one embodiment of the present invention and a powder of a compound A (e.g., calcium carbonate) to carry out a solid-phase reaction.
[0071] The zirconia-based composite oxide dielectric according to one embodiment of the present invention can be synthesized by firing at a lower temperature than that of the zirconia-based composite oxide dielectric made from conventional zirconium oxide powder. The firing temperature for synthesizing the conventional zirconia-based composite oxide dielectric made from zirconium oxide powder is generally 800°C or higher. For example, in Japanese Patent No. 5387800, calcium zirconate is obtained by firing zirconium oxide powder and calcium carbonate powder at 1200°C. However, since the zirconia-based composite oxide dielectric according to one embodiment of the present invention uses the zirconium oxide powder according to one embodiment of the present invention as a raw material, it can be synthesized by firing at a relatively low temperature, for example, from 700°C to 800°C, more specifically, from 750°C to 780°C. The temperature rise time in firing when synthesizing the zirconia-based composite oxide dielectric is preferably 2.5 hours to 5 hours, and the temperature retention time is preferably 2.5 hours to 5 hours.
[0072] In addition, the zirconia-based composite oxide dielectric is preferably in the form of a powder from the viewpoint of forming a uniform thin dielectric layer in lamination of MLCC. That is, one embodiment of the present invention is a zirconia-based composite oxide dielectric powder containing the above-mentioned zirconia-based composite oxide dielectric. The average primary particle size of the zirconia-based composite oxide dielectric powder is preferably 5.0 to 100.0 nm, more preferably 10.0 to 30.0 nm, and further preferably 15.0 to 25.0 nm.
[0073] Here, the zirconia-based composite oxide dielectric powder may contain other components as long as it is mainly composed of zirconia-based composite oxide. The ratio of the zirconia-based composite oxide contained in the zirconia-based composite oxide dielectric powder is preferably 85 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, particularly preferably 99 mass% or more, and most preferably 100 mass% based on the total mass of the zirconia-based composite oxide dielectric powder. Here, examples of other components include hafnium oxide.
[0074] The zirconia-based composite oxide dielectric material according to one embodiment of the present invention can be suitably used for dielectric layers made of ceramic in a multilayer ceramic capacitor.
[0075] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims. EXAMPLES
[0076] The effects of the present invention will be explained using the following examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following manufacturing examples and examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the technical scope of the present invention is not limited only to the following examples. The ratios of the raw materials used as the solution or dispersion (units: "parts by mass", "% by mass") are all values calculated as solid content. Unless otherwise specified, each operation was performed at room temperature (25°C).
[0077] [Production of zirconium oxide powder] According to the manufacturing method described below, zirconium oxide powders of Examples 1 to 3 and Comparative Examples 1 to 4 were manufactured.
[0078] <Example 1> Zirconium oxychloride octahydrate (ZrOCl2·8H2O) was dissolved in ion-exchanged water to a concentration of 50 g / l as zirconium oxide, to obtain 1 L of stock solution. The stock solution was heated to raise the liquid temperature to 90°C, and then 100 g of 10% ammonium carbonate solution was added to the stock solution to obtain a slurry. Next, while stirring the slurry, 25% ammonia water was added until the pH of the slurry reached 9.0. The pH of the slurry (liquid temperature: 60°C) was confirmed using a pH meter (HORIBA, Ltd., portable pH meter LAQUA D-210P).
[0079] The slurry was then filtered and washed to obtain a precipitate of a zirconium oxide precursor containing almost no impurities such as chloride ions. The filtration and washing were carried out as follows. First, the slurry was pressure filtered using a commercially available filter press or other device to obtain a solid component (filtration process). Next, the obtained solid component was repulped and washed with 10% ammonia water (washing process). These filtration and washing processes were repeated three times in this order, after which a further filtration process was carried out, and the obtained solid component was repulped and washed with ion-exchanged water, and finally, a filtration process was carried out again.
[0080] The zirconium oxide precursor obtained by the above wet method was dried at 120° C. for 6 hours while flowing carbon dioxide gas into a dryer at 100 cc / min.
[0081] Next, the dried zirconium oxide precursor was calcined in a tubular furnace (manufactured by Asahi Rika Seisakusho Co., Ltd.) under the following calcination conditions: the temperature was raised from room temperature to 400°C (calcination temperature) over 3 hours, and the temperature was maintained at 400°C (calcination temperature) for 3 hours, to obtain a calcined powder. The calcination was performed while flowing CO2 gas into the tubular furnace at 300cc / min. Next, the particle size of the calcined powder was adjusted using a hammer mill device to obtain a powder with a specific surface area (SSA) of 110m 2 / g of zirconium oxide powder was obtained.
[0082] <Example 2> The zirconium oxide powder of Example 2 was obtained in the same manner as in Example 1, except that the firing conditions were a 3-hour temperature rise from room temperature to 425°C, a 3-hour hold at 425°C, and an air atmosphere during firing. The specific surface area (SSA) of the zirconium oxide powder of Example 2 was 90 m 2 / g.
[0083] <Example 3> The zirconium oxide powder of Example 3 was obtained in the same manner as in Example 1, except that the zirconium oxide precursor obtained by the wet method was not dried, and the temperature was raised from room temperature to 330°C over 3 hours and then maintained at 330°C for 3 hours. The specific surface area (SSA) of the zirconium oxide powder of Example 3 was 140 m 2 / g.
[0084] <Comparative Example 1> The zirconium oxide powder of Comparative Example 1 was obtained in the same manner as in Example 1, except that an ammonium sulfate solution was used instead of the ammonium carbonate solution, drying treatment was not performed, and carbon dioxide was not introduced, and the temperature was raised from room temperature to 700°C in an air atmosphere over 3 hours, and the temperature was maintained at 700°C for 3 hours. The specific surface area (SSA) of the zirconium oxide powder of Comparative Example 1 was 30 m 2 The zirconium oxide powder of Comparative Example 1 corresponds to the zirconium oxide powder produced by the method described in the Examples of Patent Document 4 (JP Patent Publication 2007-15898 A).
[0085] <Comparative Example 2> A zirconium oxide powder of Comparative Example 2 was obtained in the same manner as in Example 1, except that an ammonium sulfate solution was used instead of the ammonium carbonate solution, drying treatment was not performed, and carbon dioxide was not introduced, and the temperature was raised from room temperature to 500°C in a superheated steam atmosphere over 3 hours, and the temperature was maintained at 500°C for 3 hours. The specific surface area (SSA) of the zirconium oxide powder of Comparative Example 2 was 60 m 2 / g.
[0086] <Comparative Example 3> The zirconium oxide powder of Comparative Example 3 was obtained in the same manner as in Example 1, except that an ammonium sulfate solution was used instead of an ammonium carbonate solution, drying treatment was performed in an air atmosphere without inflowing carbon dioxide gas, and firing treatment was performed under firing conditions of heating from room temperature to 700°C in an air atmosphere without inflowing carbon dioxide gas and holding at 700°C for 3 hours. The specific surface area (SSA) of the zirconium oxide powder of Comparative Example 3 was 30 m 2 / g.
[0087] <Comparative Example 4> The zirconium oxide powder of Comparative Example 2 was obtained in the same manner as in Example 1, except that an ammonium sulfate solution was used instead of the ammonium carbonate solution, drying was not performed, and carbon dioxide was not introduced, and the firing treatment was performed under the firing conditions of raising the temperature from room temperature to 400°C in a superheated steam atmosphere over 3 hours and maintaining the temperature at 400°C for 3 hours. The specific surface area (SSA) of the zirconium oxide powder of Comparative Example 4 was 110 m 2 / g.
[0088] [Measurement of specific surface area (SSA)] First, as a pretreatment, 1.5 g of the zirconium oxide powder was subjected to vacuum degassing and heat treatment at 370°C for 40 minutes in order to remove moisture and the like adhering to the pores and surface of the zirconium oxide powders of Examples 1 to 3 and Comparative Examples 1 to 4. Next, the specific surface area was calculated by the BET single point method using a gas adsorption pore distribution measuring instrument NOVA-touch (manufactured by Anton Paar). Specifically, the pretreated zirconium oxide powder was immersed in liquid nitrogen, and nitrogen gas was supplied, which caused nitrogen molecules to physically adsorb onto the particle surfaces of the zirconium oxide. Based on this, the pressure and amount of adsorption at that time were measured to obtain the specific surface area (measurement range: 0.01 m). 2 / g~, adsorbed gas; N 2、 Refrigerant (temperature): Liquid nitrogen (-195.8℃).
[0089] [Evaluation of zirconium oxide powder] The change in concentration of carbon dioxide evolved from the zirconium oxide powders obtained in Examples 1 to 3 and Comparative Examples 1 to 4 was measured by a thermal evolved gas analysis method (TPD-MS method).
[0090] The analysis was carried out as follows. First, 50 mg of each zirconium oxide powder obtained in Examples 1 to 3 and Comparative Examples 1 to 4 was placed in a glass tube passed through an electric furnace of a heating device equipped with a temperature controller, and high-purity helium (He) gas was flowed at 50 cc / min for 15 minutes. Next, the temperature was raised to about 1000°C at a heating rate of 10°C / min in a simulated air (20% O2 / He) atmosphere, and the CO2 gas generated during the heating was continuously measured using a mass spectrometer (Shimadzu Corporation, GCMS-QP2020). From the results of the measurement, the maximum desorption temperature and the amount of carbon dioxide desorbed from the zirconium oxide powder obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were obtained. The results are shown in Table 1. Also, the temperature-programmed desorption spectrum obtained from the measurement results is shown in FIG. 1.
[0091] [Table 1]
[0092] The zirconium oxide powders of Examples 1 to 3 had a maximum desorption temperature of 520° C. or more, whereas the zirconium oxide powders of Comparative Examples 1 to 4 had a maximum desorption temperature of less than 520° C. Furthermore, the zirconium oxide powders of Examples 1 to 3 had a carbon dioxide desorption amount of 0.4 mass% or more, whereas the zirconium oxide powders of Comparative Examples 1 to 4 had a carbon dioxide desorption amount of less than 0.4 mass%. From these results, it is considered that more carbon dioxide is adsorbed on the particle surfaces of the zirconium oxide powders of Examples 1 to 3 compared to Comparative Examples 1 to 4.
[0093] [Production of zirconia-based composite oxide dielectrics] Using each of the zirconium oxide powders obtained in Examples 1 to 3 and Comparative Examples 1 to 4, calcium zirconate (CaZrO3), which is a zirconia-based composite oxide dielectric, was synthesized according to the following method.
[0094] Each zirconium oxide powder and calcium carbonate powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed so that the amount converted to CaZrO3 was 30 g and the atomic ratio of Ca / Zr was 1.0, and added to 300 ml of an aqueous solution containing 0.6 g of an anionic water dispersant (manufactured by Kao Corporation, product name Kaocera 2020).The aqueous solution was then mixed for 20 hours in a ball mill using zirconia balls (manufactured by Nikkato Corporation, YTZ, ball diameter 1 mm) to produce a slurry.
[0095] The slurry was dried at 120°C for 8 hours to obtain a dried powder, which was then heated to 770°C over 3 hours in a small electric furnace (manufactured by Yamato Scientific Co., Ltd.) and fired at 770°C for 3 hours, thereby synthesizing calcium zirconate using the zirconium oxide powder of each Example and Comparative Example as a raw material.
[0096] [Evaluation of calcium zirconate] Each calcium zirconate synthesized using each zirconium oxide powder of Examples 1 to 3 and Comparative Examples 1 to 4 as a raw material was measured using X-ray diffraction (XRD).
[0097] X-ray diffraction was performed by measuring the X-ray diffraction pattern of 1 g of each calcium zirconate using an automatic powder X-ray diffractometer (Rigaku Corporation, RINT2000) with CuKα as the X-ray source under the following conditions: tube current 40 mA, tube voltage 30 kV, 2θ = 20.0° to 70.0°, step width: 0.02°, measurement speed: 0.03° / sec. The measurement results are shown in Figures 2 and 3.
[0098] As shown in Fig. 3, in the calcium zirconate prepared from the zirconium oxide powders of Comparative Examples 1 and 2, peaks derived from the raw materials zirconium oxide and calcium carbonate were observed (peaks indicated by arrows) in addition to peaks derived from calcium zirconate. On the other hand, in the calcium zirconate prepared from the zirconium oxide powders of Examples 1 to 3, as shown in Fig. 2, in addition to peaks derived from calcium zirconate, no peaks derived from zirconium oxide and calcium carbonate observed in Comparative Examples 1 and 2 were observed.
[0099] That is, it was found that when the zirconium oxide powders of Examples 1 to 3 were used, calcium zirconate could be synthesized without leaving unreacted raw materials even at a relatively low firing temperature of 770° C. On the other hand, it was found that when the zirconium oxide powders of Comparative Examples 1 and 2 were used, unreacted zirconium oxide and calcium carbonate remained when the firing temperature was about 770° C.
Claims
1. A zirconium oxide powder having a maximum carbon dioxide desorption temperature of 520°C or higher.
2. 2. The zirconium oxide powder according to claim 1, wherein the amount of carbon dioxide desorbed from the powder at 25° C. to 1000° C. is 0.4 mass % or more.
3. 2. The zirconium oxide powder according to claim 1, wherein the maximum peak of the desorption rate of carbon dioxide in a temperature programmed desorption spectrum of carbon dioxide is 100° C. or lower.
4. 2. The zirconium oxide powder according to claim 1, wherein a maximum peak of a carbon dioxide desorption rate in a temperature programmed desorption spectrum of carbon dioxide is 5.0 mass ppm / sec or more.
5. BET specific surface area is 80m 2 The zirconium oxide powder according to claim 1, wherein the zirconium oxide powder has a molecular weight of 1 / g or more.
6. A zirconia-based composite oxide dielectric material, which is made from the zirconium oxide powder according to any one of claims 1 to 5.
7. The zirconia-based composite oxide dielectric material according to claim 6 , which contains calcium.
8. A zirconia-based composite oxide dielectric powder comprising the zirconia-based composite oxide dielectric according to claim 6.
Citation Information
Patent Citations
Method for manufacturing zirconium oxide powder and zirconium oxide powder
JP2007015898A
Multilayer ceramic capacitor
JP2015195352A
Multilayer ceramic capacitor
JP2017028254A
Zirconium oxide powder and method of producing the same
JP2019202901A